Development of Positive Reinforcement-Based Economic Token Media to Improve Children's Discipline - Ni Luh Putu Eliawati; Shofiyanti Nur Zuama; Jane Mariem Monepa; Nurhayati Nurhayati (Journal of Educational Sciences, 2026)
This study aims to develop an economic token-based media using positive reinforcement to improve children's discipline. The background of this study stems from the problem of low discipline among children, such as children often arriving late, not tidying up their toys, and not following the teacher's instructions when doing tasks. This research uses the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were 23 children in group B. This Economic Token Media was validated by two subject matter experts and media experts. The two experts gave it a validation score of 88.23% from the media expert and 100% from the subject matter expert. This media has been tested on 15 children in group B aged 5-6 years. From the test results, a feasibility score was obtained with a percentage of BSB 62.22%, BSH 26.66%, MB 11.11%, and BB 0%. The use of economic token media has been proven to be effective in improving children's discipline and is suitable for testing on children. It is also very safe to use and not harmful to children.